An injection molded ultra-high strength metal-polymer joint and a preparation method thereof
By using a strong oxidized metal ion saline solution and ultrasonic vibration to treat the surface of the aluminum alloy by using a strong oxidized metal ionic saline solution and ultrasonic alcohol, the existing connector is solved in the hybrid solution of amino sircitanane and polyethylene glycol, and the existing joints are solved. Based on the problem of low strength, high-intensity metal-polymer connections are realized.
Patent Information
- Application Number
- CN202311820320.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The existing injection molded metal-polymer joints have low bond strength and are difficult to meet high strength requirements.
By placing an aluminum alloy embedded parts to be treated in a strong oxidized metal ion saline solution for ultrasonic vibration treatment, the micro-nano-level structure is generated, and then secondary treatment in the mixed solution of amino silicane and polyethylene alcohol to achieve metal metal -The mechanical interoperability and chemical combination of polymer.
The stretch shear strength of the metal-polymer connector is significantly improved, reaching 50-54MPa, which is much higher than the intensity of existing injection molding joints.
Smart Images

Figure CN117774218B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dissimilar metal-polymer interface bonding, in particular to an injection-molded ultra-high strength metal-polymer joint and a preparation method thereof. Background Art
[0002] Based on the requirements of environmental protection and sustainable development, metal-polymer composites are gaining more and more attention in the fields of aerospace and rail transportation due to their excellent specific strength, specific stiffness and recyclability. Usually, metal-polymer composites are made of light alloys and polymers. The polarity difference between the two materials is very large, and the metal-polymer interface bonding strength is low.
[0003] In order to improve the metal-polymer interface bonding strength, researchers have conducted a series of studies on interface bonding using processes such as mechanical connection, adhesive bonding, hot pressing connection, stir friction welding, and laser welding. The metal / polymer bonding strength is also improved through methods such as metal surface pretreatment, polymer modification, and insertion of intermediate layers.
[0004] However, in the metal-polymer bonding process, mechanical connection joints are prone to stress concentration and have a short service life; adhesive bonding joints have poor water absorption and are prone to environmental pollution; hot pressing connection processes have problems such as long bonding time and serious energy waste; various types of welded joints have poor dimensional stability and polymers are prone to burning. Among them, injection molding has the advantages of high molding efficiency, diversified product shapes, and extremely high energy utilization, but in actual production processes, the metal-polymer interface bonding strength is much lower than the process described above. Therefore, how to enhance the bonding strength of injection molded metal-polymer joints has become a technical problem for researchers in this field.
[0005] In order to improve the strength of injection molded metal-polymer joints, researchers have carried out a series of research methods, which can be summarized into two methods: metal surface morphology treatment and metal-polymer interface modification. Among them, metal surface morphology treatment can improve the roughness of the metal surface and achieve metal-polymer mechanical interlocking, mainly including metal surface sandblasting, micro-nanosecond laser etching, chemical corrosion, anodizing and micro-arc oxidation. Metal-polymer interface modification, by inserting intermediate active bodies, realizes the chemical bonding of metal-polymers, mainly including coating active chemical reagents, chemical vapor deposition, plasma treatment, hot water bath, etc. The combined pretreatment of the above methods can achieve a significant improvement in the bonding strength of metal-polymer joints, but none of them have exceeded 40MPa.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing an injection molded metal-polymer joint. The metal-polymer joint prepared by the method has a tensile shear strength of 50-54MPa, which is much higher than the strength of existing metal-polymer injection molded joints.
[0008] In a first aspect, the present invention provides a method for preparing an injection molded metal-polymer joint, comprising the following steps:
[0009] S1. placing the aluminum alloy insert to be treated in a strong oxidizing metal ion salt solution and subjecting it to ultrasonic vibration treatment to chemically corrode the surface of the aluminum alloy;
[0010] S2, placing the aluminum alloy insert after chemical corrosion in a mixed solution of aminosilane and polyvinyl alcohol to perform secondary treatment on the aluminum alloy surface;
[0011] S3, placing the aluminum alloy insert after secondary treatment in the mold cavity, closing the mold and injecting the polymer to obtain a metal-polymer joint;
[0012] The aqueous solution of strong oxidizing metal ion salt includes any one or more aqueous solutions of FeCl3, CuCl2, NaMnO4 and Na2CrO4.
[0013] In order to improve the bonding strength of injection molded metal-polymer joints, the present invention first places the metal insert to be treated in a strongly oxidizing metal ion salt solution, and simultaneously performs ultrasonic vibration treatment to generate a micro-nano structure on the metal surface, thereby enhancing the mechanical interlocking effect of the metal-polymer; then, the chemically corroded metal insert is placed in a mixed solution of aminosilane and polyvinyl alcohol, and the surface is subjected to secondary treatment. Under the action of aminosilane and polyvinyl alcohol, not only can the chemical bonding of the metal-polymer be achieved, but also the wettability of the metal surface can be improved, the injection molding time can be reduced, the injection molding efficiency can be improved, and the super-strong connection of the injection molded joint can be achieved.
[0014] The preparation method of the present invention is suitable for metal-polymer joints combined in the form of injection molding, and the metal here is preferably an aluminum alloy. Studies have shown that the tensile shear strength of the aluminum alloy-polymer joint prepared by the method of the present invention can reach 50-54MPa, which is much higher than the strength of the existing metal-polymer injection molding joint.
[0015] On the basis of the above technical solution, it is further preferred that in step S1, the concentration of the aqueous solution of strongly oxidizing metal ion salt is 10-20wt.%, and the concentration can be selected according to the oxidizing property of the metal ion salt solution. For metal ion salts with low oxidizing property, a solution with slightly higher concentration can be selected, and for metal ion salts with high oxidizing property, a solution with lower concentration can be selected; and the final use concentration needs to be determined according to the surface area of the metal to ensure that the surface morphology of the metal corrosion is not affected by the reduction in metal ion concentration.
[0016] Specifically, in step S1, during the chemical etching, the temperature is controlled to be 40-80° C. and the time is 10-20 minutes.
[0017] At this temperature, ultrasonic vibration treatment of the aluminum alloy surface can not only increase the rate of generation of micro-nano structure on the aluminum alloy surface, but also ensure the uniformity of the micro-nano structure on the aluminum alloy surface. It can not only enhance the mechanical interlocking effect of metal-polymer, but also provide a treatment basis for secondary treatment of the aluminum alloy surface.
[0018] The chemical reaction principle involved in step S1 of the present invention is as follows:
[0019]
[0020] On the basis of the above technical solution, more preferably, in step S1, after chemically etching the surface of the aluminum alloy, the aluminum alloy needs to be placed in deionized water and anhydrous ethanol for ultrasonic cleaning in sequence to remove the strong oxidizing metal ion salt solution remaining on the surface of the aluminum alloy, and then taken out and dried using a nitrogen gun;
[0021] Preferably, the ultrasonic cleaning time is 10-20 min;
[0022] Preferably, during the ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 80-100W and the frequency is 30-50KHz.
[0023] As a preferred embodiment of the present technical solution, in step S2, in the mixed solution of aminosilane and polyvinyl alcohol, the concentration of aminosilane is 1-5wt.%, and the concentration of polyvinyl alcohol is 0.1-0.5wt.%;
[0024] Preferably, the aminosilane includes any one or more of KH-550, KH-792 and KH-892;
[0025] Preferably, the degree of polymerization of the polyvinyl alcohol is 1000-2000 to ensure the viscosity of the aqueous solution.
[0026] Specifically, the preparation method of the mixed solution of aminosilane and polyvinyl alcohol is:
[0027] Dissolve polyvinyl alcohol in deionized water, heat to 80-100° C. under magnetic stirring to fully swell for 1-3 hours, and prepare a polyvinyl alcohol solution with a concentration of 1-5 wt.%, wherein the speed of the magnetic stirring is 30-50 rpm / min to maximize the dissolution rate of the polyvinyl alcohol;
[0028] Then, the aminosilane is dropped into a premixed solution of anhydrous ethanol and deionized water, and the polyvinyl alcohol solution is added under magnetic stirring, and stirring is continued for 30-40 minutes to reduce the precipitation of polyvinyl alcohol polymer to obtain a mixed solution of aminosilane and polyvinyl alcohol, wherein the volume ratio of anhydrous ethanol to deionized water is 5:(1-2), and the speed of magnetic stirring is 10-15rpm / min.
[0029] As a preferred embodiment of the present technical solution, during the dissolution process of polyvinyl alcohol, polyvinyl alcohol is placed in deionized water and slowly heated at a rate lower than 10°C / min. When the temperature reaches 80-100°C, the temperature is maintained for 1-3h and then slowly cooled at a rate lower than 5°C / min.
[0030] As a preferred embodiment of the present technical solution, in step S2, the dried aluminum alloy insert is placed in a mixed solution of aminosilane and polyvinyl alcohol and immersed for 10-20 minutes. After the immersion, in order to ensure the activity of aminosilane and polyvinyl alcohol, the aluminum alloy is usually placed for no more than 12 hours. Therefore, after the immersion is completed, the aluminum alloy insert should be placed in an oven as soon as possible and baked at 80-110°C for 10-20 minutes, so that the Si-OH in the aminosilane (such as KH-892) and the AlOOH on the surface of the aluminum alloy are chemically bonded to produce Si-O-Al and H2O, so that the KH-892 nanonetwork is bonded to the surface of the aluminum alloy, thereby completing the secondary treatment of the aluminum alloy surface.
[0031] As a preferred embodiment of the present technical solution, in step S1, the present invention does not strictly limit the working power and frequency of the ultrasonic vibration machine during ultrasonic vibration, wherein the working power is preferably 110-130W and the frequency is preferably 30-50KHz.
[0032] In the second aspect, the present invention also discloses a metal-polymer joint in injection molding prepared by the above method, which should also belong to the protection scope of the present invention. Specifically, the tensile shear strength of the metal-polymer joint is 50-54 MPa.
[0033] The method for preparing the injection-molded metal-polymer joint of the present invention has at least the following technical effects:
[0034] In the preparation method of the injection-molded metal-polymer joint of the present invention, first, the aluminum alloy insert to be treated is placed in a strong oxidizing metal ion salt solution, and ultrasonic vibration treatment is performed to produce a micro-nano structure on the surface of the aluminum alloy to enhance the mechanical interlocking effect of the metal-polymer; then, the aluminum alloy insert after chemical corrosion is placed in a mixed solution of aminosilane and polyvinyl alcohol, and the surface is treated for a second time. Under the action of aminosilane and polyvinyl alcohol, on the one hand, the wettability of the aluminum alloy surface is transformed, the flow rate of the polymer on the aluminum alloy surface is increased, and the polymer and the metal interface can be fully combined in a very short time; on the other hand, aminosilane and the aluminum alloy surface can produce Si-O-Al bonds, and the -NH2 in aminosilane and the -OH in polyvinyl alcohol can produce strong hydrogen bonds with the -O- in the polymer, so that the aluminum alloy and the polymer are chemically combined to achieve the super strong connection of the injection-molded joint. Studies have shown that the tensile shear strength of the metal-polymer joint prepared by the method of the present invention can reach 50-54MPa, which is much higher than the strength of the existing metal-polymer injection-molded joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 The electron microscope images of the aluminum alloy surface corrosion and ultrasonic vibration corrosion of the present invention;
[0037] Figure 2 This is a comparison chart of interface bonding strength of Examples 1-3 and Comparative Examples 1-10 of the present invention;
[0038] Figure 3 XPS spectra of chemical bonds produced under different treatment conditions of the present invention;
[0039] Figure 4 FTIR spectra of chemical bonds produced under different treatment conditions of the present invention;
[0040] Figure 5 is the roughness of the aluminum alloy surface under different treatment conditions of the present invention;
[0041] Figure 6 It is the wetting property of the aluminum alloy surface under different treatment conditions of the present invention. DETAILED DESCRIPTION
[0042] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0043] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] S11, placing the aluminum alloy insert to be treated in a 15wt.% FeCl3 aqueous solution, and treating it at 45°C for 15 minutes under the vibration of an ultrasonic vibrator with a working power of 120W and a frequency of 4KHz to chemically corrode the aluminum alloy surface;
[0047] After chemically corroding the surface of the aluminum alloy, it was immersed in a container filled with deionized water and ultrasonically cleaned for 15 minutes, and then immersed in anhydrous ethanol and ultrasonically cleaned for 15 minutes. After being taken out, it was dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine was 90W and the frequency was 40KHz.
[0048] S12, placing the dried aluminum alloy insert in a mixed solution of 3wt.% aminosilane (KH-892) and 0.3wt.% polyvinyl alcohol (degree of polymerization 2000) for 15 minutes, and then placing the aluminum alloy in an oven and baking it at 90°C for 15 minutes to complete the secondary treatment of the aluminum alloy surface;
[0049] S13, placing the aluminum alloy insert after secondary treatment in the mold cavity, closing the mold and injection molding the polymer to obtain a metal-polymer joint, and the injection molding parameters are shown in Table 1.
[0050] Table 1 Injection molding parameters
[0051]
[0052] Example 2
[0053] S21, placing the aluminum alloy insert to be treated in a 20wt.% FeCl3 aqueous solution, and treating it at 50°C for 10 minutes under the vibration of an ultrasonic vibrator with a working power of 120W and a frequency of 40KHz to chemically corrode the surface of the aluminum alloy;
[0054] After chemically corroding the surface of the aluminum alloy, immerse it in a container filled with deionized water and perform ultrasonic cleaning for 20 minutes, then immerse it in anhydrous ethanol and perform ultrasonic cleaning for 20 minutes. After being taken out, it is dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 100W and the frequency is 30KHz.
[0055] S22, placing the dried aluminum alloy insert in a mixed solution of 5wt.% aminosilane (KH-892) and 0.5wt.% polyvinyl alcohol (degree of polymerization 2000) for 20 minutes, and then placing the aluminum alloy in an oven and baking it at 80°C for 20 minutes to complete the secondary treatment of the aluminum alloy surface;
[0056] S23, placing the aluminum alloy insert after secondary treatment in the mold cavity, closing the mold and injection molding the polymer to obtain a metal-polymer joint.
[0057] Example 3
[0058] S31, placing the aluminum alloy insert to be treated in a 10wt.% FeCl3 aqueous solution, and treating it at 50°C for 10 minutes under the vibration of an ultrasonic vibrator with a working power of 120W and a frequency of 40KHz to chemically corrode the surface of the aluminum alloy;
[0059] After chemically corroding the surface of the aluminum alloy, it was immersed in a container filled with deionized water and ultrasonically cleaned for 10 minutes, and then immersed in anhydrous ethanol and ultrasonically cleaned for 10 minutes. After being taken out, it was dried with a nitrogen gun. During ultrasonic cleaning, the working power of the ultrasonic cleaning machine was 90W and the frequency was 40KHz.
[0060] S32, placing the dried aluminum alloy insert in a mixed solution of 5wt.% aminosilane (KH-892) and 0.5wt.% polyvinyl alcohol (degree of polymerization 2000), fully immersing for 15 minutes, then placing the aluminum alloy in an oven and baking at 100°C for 15 minutes to complete the secondary treatment of the aluminum alloy surface;
[0061] S33, placing the aluminum alloy insert after secondary treatment in the mold cavity, closing the mold and injection molding the polymer to obtain a metal-polymer joint.
[0062] Comparative Example 1
[0063] Only the metal insert is sandpaper ground and alcohol cleaned, then the aluminum alloy insert is placed in the mold cavity, the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0064] Comparative Example 2
[0065] The aluminum alloy insert is ground with sandpaper, and then immersed in an aminosilane solution with a concentration of 3 wt.%, and finally the aluminum alloy insert is placed in a mold cavity, and the mold is closed and a polymer is injection-molded to obtain a metal-polymer joint.
[0066] Comparative Example 3
[0067] The aluminum alloy insert is ground with sandpaper, and then immersed in a mixed solution with an aminosilane concentration of 3wt.% and a polyvinyl alcohol concentration of 0.3wt.%, and finally the aluminum alloy insert is placed in a mold cavity, and the mold is closed and a polymer is injection-molded to obtain a metal-polymer joint.
[0068] Comparative Example 4
[0069] The aluminum alloy insert is chemically corroded using a strongly oxidizing metal ion salt solution (same as step S11 in Example 1, except that ultrasonic vibration is not performed);
[0070] After alcohol cleaning and drying, the aluminum alloy insert is placed in the mold cavity, and the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0071] Comparative Example 5
[0072] The aluminum alloy insert is chemically corroded using a strongly oxidizing metal ion salt solution (same as step S11 in Example 1, except that ultrasonic vibration is not performed);
[0073] Then, the aluminum alloy insert is placed in an aminosilane solution with a concentration of 3 wt.% for dipping. Finally, the aluminum alloy insert is placed in a mold cavity, and the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0074] Comparative Example 6
[0075] The aluminum alloy insert is chemically corroded using a strongly oxidizing metal ion salt solution (same as step S11 in Example 1, except that ultrasonic vibration is not performed);
[0076] Then, the aluminum alloy insert is immersed in a mixed solution with an aminosilane concentration of 3wt.% and a polyvinyl alcohol concentration of 0.3wt.%, and finally, the aluminum alloy insert is placed in a mold cavity, and the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0077] Comparative Example 7
[0078] Chemically corrode the aluminum alloy insert using a strong oxidizing metal ion salt solution (same as step S11 in Example 1);
[0079] After alcohol cleaning and drying, the aluminum alloy insert is placed in the mold cavity, and the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0080] Comparative Example 8
[0081] Chemically corrode the aluminum alloy insert using a strong oxidizing metal ion salt solution (same as step S11 in Example 1);
[0082] Then, the aluminum alloy insert is placed in an aminosilane solution with a concentration of 3 wt.% for dipping. Finally, the aluminum alloy insert is placed in a mold cavity, and the mold is closed and the polymer is injection-molded to obtain a metal-polymer joint.
[0083] Comparative Example 9
[0084] Use NaOH to replace the strong oxidizing metal ion salt solution in Example 1,
[0085] The other steps and parameters are basically the same as those in Example 1.
[0086] Comparative Example 10
[0087] γ-glycidyloxypropyltrimethoxysilane KH-560 is used to replace the mixed solution of aminosilane and polyvinyl alcohol in Example 1;
[0088] The other steps and parameters are basically the same as those in Example 1.
[0089] Figure 1 The present invention only studies the influence of chemical corrosion and chemical corrosion under ultrasonic vibration on the surface microstructure of aluminum alloy.
[0090] Depend on Figure 1 It can be seen that after being treated with the strong oxidizing metal ion salt solution of the present invention, only a micron structure can be produced on the aluminum alloy surface, while when the strong oxidizing metal ion salt solution treatment is supplemented with ultrasonic vibration treatment, an obvious micro-nano structure will be produced on the aluminum alloy surface.
[0091] In order to further study the effects of different treatment methods on the tensile shear strength of metal-polymer joints, the present invention measured the tensile shear strength of the metal-polymer joints obtained in Examples 1-3 and Comparative Examples 1-10. The test results are shown in Tables 2 and Figure 2 shown.
[0092] Table 2 Tensile shear strength test results
[0093] Serial number Tensile shear strength (MPa) Example 1 53.9 Example 2 51.2 Example 3 50.6 Comparative Example 1 2.96 Comparative Example 2 4.39 Comparative Example 3 9.74 Comparative Example 4 20.6 Comparative Example 5 26.9 Comparative Example 6 36.7 Comparative Example 7 31.8 Comparative Example 8 35.5 Comparative Example 9 22.5 Comparative Example 10 28.4
[0094] Combining Table 2 and Figure 2 It can be seen that the method of the present invention of corrosion treatment of the aluminum alloy surface using a mixed solution of a strongly oxidizing metal ion salt solution, aminosilane and polyvinyl alcohol can significantly improve the metal-polymer interface bonding strength, and its tensile shear strength can reach 50-54MPa, which is much higher than the strength of existing metal-polymer injection molding joints.
[0095] Comparative Example 8 uses an ethanol solution of aminosilane to replace the mixed solution of aminosilane and polyvinyl alcohol in Example 1. The strength of the obtained metal-polymer injection molded joint is relatively poor compared with that of Example 1. The reason may be that there is no effect of PVA. The strength of the O...H2N hydrogen bond generated by the KH-892 nanonetwork and the polymer is stronger than the OH...O... generated by the KH-892 and PVA combined nanonetwork and the polymer.
[0096] The strength of NH2 complex hydrogen bond is low.
[0097] In Control Example 9, NaOH was used to replace the strongly oxidizing metal ion salt solution in Example 1. Although the strength of the obtained metal-polymer injection molded joint was improved to a certain extent, its tensile shear strength still needed to be improved compared with Example 1. This may be because the surface roughness obtained by NaOH corrosion was too low, and no cross-scale mesh surface structure was generated, the mechanical interlocking effect was small, and the metal-polymer interface bonding strength was lower than that of the joint treated with ultrasonic FeCl3.
[0098] Control Example 10 uses γ-glycidyloxypropyltrimethoxysilane KH-560 to replace the mixed solution of aminosilane and polyvinyl alcohol in Example 1. The reason why the strength of the resulting metal-polymer injection molding joint is relatively poor compared with Example 1 may be that KH-560 produces Si-O-Al bonds with the Al surface, so that the KH-560 nanonetwork is fixed on the aluminum alloy surface, but the epoxy groups inside KH-560 cannot chemically bond with COC and C=O in the polymer, and there is no chemical bonding at the interface, so the strength is relatively low.
[0099] At the same time, the present invention also analyzes the design principle of the processing method of the present invention, wherein: Figure 3 The XPS spectra of the aluminum alloy surface under different treatment conditions of the present invention are as follows: Figure 4 FTIR spectra of the aluminum alloy surface under different treatment conditions of the present invention.
[0100] Combination Figure 3-6It can be seen that after the present invention uses a strong oxidizing metal ion salt FeCl3 aqueous solution to perform ultrasonic chemical corrosion on the aluminum alloy surface, the surface roughness is significantly improved compared to before treatment, and AlOOH is generated on the surface. The present invention uses a mixed solution of aminosilane and polyvinyl alcohol to perform secondary treatment on the aluminum alloy surface. Compared with using only aminosilane solution, it can not only promote the chemical bonding between the aluminum alloy and the polymer (such as aminosilane and the aluminum alloy surface can produce Si-O-Al bonds), but also the -NH2 of aminosilane and the -OH of polyvinyl alcohol can produce complex hydrogen bonds with -O- and C=O in the polymer. In addition, under the joint action of aminosilane and polyvinyl alcohol, the wettability of the aluminum alloy surface is also transformed, the flow rate of the polymer on the aluminum alloy surface is improved, and the full bonding of the polymer and the aluminum alloy interface can be achieved in a very short time, so that the metal and the polymer are chemically bonded, and the super strong connection of the injection molding joint is achieved.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an injection molded metal-polymer joint, characterized in that: The following steps are involved: S1. placing the metal insert to be treated in a strong oxidizing metal ion salt solution and subjecting it to ultrasonic vibration treatment to chemically corrode the metal surface; S2, placing the chemically corroded metal insert in a mixed solution of aminosilane and polyvinyl alcohol to perform secondary treatment on the metal surface; S3, placing the metal insert after secondary treatment in the mold cavity, closing the mold and injecting the polymer to obtain a metal-polymer joint; Wherein, the aqueous solution of strongly oxidizing metal ion salt includes any one or more aqueous solutions of FeCl3, CuCl2, NaMnO4 and Na2CrO4; In step S1, the concentration of the strong oxidizing metal ion salt solution is 10-20wt.%; In step S1, during the chemical etching, the temperature is controlled to be 40-80°C and the time is 10-20 minutes; In step S2, in the mixed solution of aminosilane and polyvinyl alcohol, the concentration of aminosilane is 1-5wt.%, and the concentration of polyvinyl alcohol is 0.1-0.5wt.%; The aminosilane includes any one or more of KH-550, KH-792 and KH-892; The degree of polymerization of the polyvinyl alcohol is 1000-2000; The preparation method of the mixed solution of aminosilane and polyvinyl alcohol is as follows: Dissolve polyvinyl alcohol in deionized water, heat to 80-100°C under magnetic stirring to fully swell for 1-3 hours, and prepare a polyvinyl alcohol solution with a concentration of 1-5wt.%, wherein the speed of magnetic stirring is 30-50rpm / min; Drop aminosilane into a premixed solution of anhydrous ethanol and deionized water, add polyvinyl alcohol solution under magnetic stirring, and continue stirring for 30-40 minutes to obtain a mixed solution of aminosilane and polyvinyl alcohol, wherein the volume ratio of anhydrous ethanol to deionized water is 5:(1-2), and the speed of magnetic stirring is 10-15rpm / min; Place polyvinyl alcohol in deionized water, slowly increase the temperature at a rate lower than 10°C / min, maintain the temperature for 1-3h when the temperature reaches 80-100°C, and then slowly decrease the temperature at a rate lower than 5°C / min; In step S2, the dried metal insert is immersed in a mixed solution of aminosilane and polyvinyl alcohol for 10-20 minutes, and then the metal insert is placed in an oven and baked at 80-110° C. for 10-20 minutes to complete the secondary treatment of the metal surface; The metal insert is made of aluminum alloy.
2. The preparation method according to claim 1, characterized in that: In step S1, after chemically corroding the metal surface, the metal surface is placed in deionized water and anhydrous ethanol for ultrasonic cleaning in sequence, and then taken out and dried using a nitrogen gun; The ultrasonic cleaning time is 10-20 minutes; During the ultrasonic cleaning, the working power of the ultrasonic cleaning machine is 80-100W and the frequency is 30-50KHz.
3. The preparation method according to claim 1, characterized in that: In step S1, during the ultrasonic vibration, the working power of the ultrasonic vibration machine is 110-130W and the frequency is 30-50KHz.
4. An injection molded metal-polymer joint, characterized in that Prepared by the preparation method according to any one of claims 1 to 3, the metal-polymer joint has a tensile shear strength of 50-54 MPa.
Citation Information
Patent Citations
Preparation method of metal resin complex and metal resin complex prepared thereby
CN103448202A
Metal-plastic complex and manufacturing method thereof
CN104479152A
Anti-corrosion super-smooth capillary aluminum pipe and preparation method and device thereof
CN113819341A